Implementasi Standar Kompetensi Manajerial Kepala Madarasah Aliyah Negeri 5 Mandailing Natal Bidang Sarana dan Prasarana Pendidikan - Sakban Sakban; Salman Salman; Wismanto Wismanto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
AbstractThe problem in this research is that the implementation of the managerial competency standards for the head of Madrasah Aliyah Negeri 5 Mandailing Natal in the field of educational facilities and facilities has not clearly seen the management carried out by the principal. This study aims to determine the achievement of the implementation of the managerial competency standards for the head of Madrasah Aliyah Negeri 5 Mandailing Natal in the field of educational facilities and facilities. The purpose of this research is to enrich the scientific paradigm in the field of Islamic Education Management, especially the study of the managerial behavior of madrasah principals. The research approach used in this research is descriptive qualitative research with data collection techniques also carried out through observation, in-depth interviews and documentation. The results of this study indicate that the implementation of the policy for the Managerial Competency Standards for the Principal of Madrasah Aliyah Negeri 5 Mandailing Natal in the field of educational facilities and facilities has been implemented optimally.